PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA TERHADAP HASIL BELAJAR KOGNITIF PENJUMLAHAN PECAHAN BERPENYEBUT TIDAK SAMA KELAS V SEKOLAH DASAR - Erdani, Putri; Masniladevi, Masniladevi; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
AbstractThe purpose of this research was to effect of PMRI on mathematics learning outcome in class V at SD N 13 Cingkariang. This research is a quasy experimental. Sampling data is taken by nonprobability sampling with total sampling. The sample of this study amounted to 54 people, with a population of 54 people. Based on the research that has been done, obtained t count > t table, 3,44 > 2.00665 with α = 0.05 is means Ho is rejected and Ha accepted, it meaning there is influence the use of PMRI  on mathematics learning outcome in class V at SDN 13 Cingkariang.Keywords:PMRI, mathematics learning outcome.